2021
DOI: 10.1039/d0ob02482a
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive host–guest chemistry and relaxation time of fluorinated cyclodextrin and arylazopyrazole-functionalized DOTA metal complexes

Abstract: Light-responsive modulation of the longitudinal (T1) and transversal (T2*) relaxation times of a fluorinated cyclodextrin has been achieved by host guest complexation with arylazopyrazole-modified metal complexes in aqueous solution. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…13−16 Similar to azobenzenes, 9,12,17−19 AAPs can change their E/Z configuration by photoisomerization using 520 nm visible or 365 nm UV light, 20−22 but are considered as superior analogues to azobenzene derivatives because of their high photostationary states of >90% for switching in both directions and their remarkably long thermal half-life times. 18,23,24 Depending on the system under investigation, the lightinduced changes of the contact angle Θ vary to a large extent. For instance, Kwon et al 25 showed for dye-sensitized TiO 2 surfaces that Θ was changed reversibly by ∼40°when the samples were irradiated with light.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13−16 Similar to azobenzenes, 9,12,17−19 AAPs can change their E/Z configuration by photoisomerization using 520 nm visible or 365 nm UV light, 20−22 but are considered as superior analogues to azobenzene derivatives because of their high photostationary states of >90% for switching in both directions and their remarkably long thermal half-life times. 18,23,24 Depending on the system under investigation, the lightinduced changes of the contact angle Θ vary to a large extent. For instance, Kwon et al 25 showed for dye-sensitized TiO 2 surfaces that Θ was changed reversibly by ∼40°when the samples were irradiated with light.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the size and polarity of AAPs and the fact that many drugs indeed contain pyrazole derivatives play important roles in expanding the applicability of these photoswitches in photopharmacology . On the basis of the high potential of AAPs for application in biological systems, numerous reports, in particular, by Fuchter, ,, Ravoo, ,, and Venkataramani, , have been published in recent years . Although this enabled novel AAP derivatives with promising photophysical and photochemical properties, the E → Z isomerization was induced with UV light in all of these AAPs.…”
mentioning
confidence: 99%
“…In fact, CDs decorated with multiple Gd ions provoke a short relaxation time. In this sense, the authors reported the synthesis of fluorinated CD (FCD), which can modulate the relaxation time of 19 F, longitudinal (T 1 ) and transversal (T* 2 ) by the light-responsive host-guest complexation with arylazopyrazole (AAP)-functionalized 1,4,7,10-tetraazacyclodo-decane-1,4,7,10-tetraacetic acid (DOTA) metal complexes (Scheme 5) [86]. FCD is a highly soluble compound that contains 21 equivalent fluorine atoms, making it a suitable contrast agent for MRI.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Representation of the photoresponsive modulation of T 1 /T* 2 relaxation time of FCD and AAP-functionalized DOTA metal complexes by host-guest interaction. Reproduced with permission from[86], RSC, 2021.…”
mentioning
confidence: 99%